Topical tenofovir protects against vaginal simian HIV infection in macaques coinfected with Chlamydia trachomatis and Trichomonas vaginalis. (27th March 2017) - Makarova, Natalia; Henning, Tara; Taylor, Andrew; Dinh, Chuong; Lipscomb, Jonathan; Aubert, Rachael; Hanson, Debra; Phillips, Christi; Papp, John; Mitchell, James; McNicholl, Janet; Garcia-Lerma, Gerardo J.; et al.
Abstract : Background: Chlamydia trachomatis and Trichomonas vaginalis, two prevalent sexually transmitted infections, are known to increase HIV risk in women and could potentially diminish preexposure prophylaxis efficacy, particularly for topical interventions that rely on local protection. We investigated in macaques whether coinfection with Chlamydia trachomatis / Trichomonas vaginalis reduces protection by vaginal tenofovir (TFV) gel. Methods: Vaginal TFV gel dosing previously shown to provide 100 or 74% protection when applied either 30 min or 3 days before simian HIV(SHIV) challenge was assessed in pigtailed macaques coinfected with Chlamydia trachomatis / Trichomonas vaginalis and challenged twice weekly with SHIV162p3 for up to 10 weeks (two menstrual cycles). Three groups of six macaques received either placebo or 1% TFV gel 30 min or 3 days before each SHIV challenge. We additionally assessed TFV and TFV diphosphate concentrations in plasma and vaginal tissues in Chlamydia trachomatis / Trichomonas vaginalis coinfected ( n  = 4) and uninfected ( n  = 4) macaques. Results: Chlamydia trachomatis / Trichomonas vaginalis coinfections were maintained during the SHIV challenge period. All macaques that received placebo gel were SHIV infected after a median of seven challenges (one menstrual cycle). In contrast, no infections were observed in macaques treated with TFV gel 30 min before SHIV challenge ( P  < 0.001). Efficacy was reduced to 60% when TFV gel was applied 3 days before SHIV challenge ( P  = 0.07). Plasma TFV and TFV diphosphate concentrations in tissues and vaginal lymphocytes were significantly higher in Chlamydia trachomatis / Trichomonas vaginalis coinfected compared with Chlamydia trachomatis / Trichomonas vaginalis uninfected macaques. Conclusion: Our findings in this model suggest that Chlamydia trachomatis / Trichomonas vaginalis coinfection may have little or no impact on the efficacy of highly effective topical TFV modalities and highlight a significant modulation of TFV pharmacokinetics.